1992
DOI: 10.1002/jcb.240500115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of monensin on the sulfation of heparan sulfate proteoglycan from endothelial cells

Abstract: Monensin is a monovalent metal ionophore that affects the intracellular translocation of secretory proteins at the level of trans-Golgi cisternae. Exposure of endothelial cells to monensin results in the synthesis of heparan sulfate and chondroitin sulfate with a lower degree of sulfation. The inhibition is dose dependent and affects the ratio [35S]-sulfate/[3H]-hexosamine of heparan sulfate from both cells and medium, with no changes in their molecular weight. By the use of several degradative enzymes (hepari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…This study did not define which of the six known heparan sulfate disaccharide isomers obtained by heparitinase digestion were present. It is tempting to speculate that in IL8-infused rats, there is, as under other experimental conditions associated with low sulfation [16], a decrease in the disaccharides bearing a sulfate ester at the 6-position of the glucosamine moiety, since this esterification is the last step of heparan sulfate synthesis that seems to occur in the trans-Golgi compartment [17]. Further studies assessing the disaccharide composition of the altered heparan sulfate are needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 96%
“…This study did not define which of the six known heparan sulfate disaccharide isomers obtained by heparitinase digestion were present. It is tempting to speculate that in IL8-infused rats, there is, as under other experimental conditions associated with low sulfation [16], a decrease in the disaccharides bearing a sulfate ester at the 6-position of the glucosamine moiety, since this esterification is the last step of heparan sulfate synthesis that seems to occur in the trans-Golgi compartment [17]. Further studies assessing the disaccharide composition of the altered heparan sulfate are needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 96%
“…Sensitivity of sulfation of gp4A4 in M monensin suggested that gp4A4 is a sulfated glycoprotein and not a proteoglycan (Sampaio et al, 1992). In addition, gp4A4 did not bind to an anion exchange resin in low salt concentrations (0.2 M NaCI), further suggesting that it is not a proteoglycan or a glycosaminoglycan (S.R.…”
Section: Discussionmentioning
confidence: 99%
“…The proteins were excised and extracted from the gel and the amount of radioactivity measured. Sulfation of gp4A4 was inhibited 70% by M monensin, which blocks sulfation of all sulfated glycoproteins and <15% by M monensin, which only inhibits sulfation of proteoglycans (Sampaio et al, 1992).…”
Section: Membrane Glycoproteinmentioning
confidence: 95%
See 1 more Smart Citation
“…Endothelial cells act as an antithrombogenic surface since they inhibit platelet adhesion, fibrinolysis and clotting . Endothelial cells also serve as a source of molecules that act to minimize the migration of the SMCs into the luminal side of the graft, thereby, reducing IH . Independent of the migratory effects of these biomolecules, they prevent the attachment of platelets to the luminal surface of the graft promoting sustained hemocompatibility .…”
Section: Introductionmentioning
confidence: 99%